The Effect of Consumer Value on Attitude Toward Green Product and Green Consumer Behavior in Organic Food - Adhitiya, Lucky; Astuti, Rifelly Dewi (IPTEK Journal of Proceedings Series, 2019)
At the moment the world market continues to change, sustainability pillars such as environment, economy and social justice have become part of marketing decision-making. Developing a marketing strategy in the midst of current environmental and economic issues has led to a focus on the importance of green marketing. Using the theory of consumption values and value-attitude-behavior model, this research proposes to explore the green consumer behavior for green products in Indonesia. Attitude toward green product and consumer values such as functional value (price and quality), social value, conditional value, epistemic value, emotional value, and environmental value were used to study the green consumer behavior for green products. This study developed a research model and empirically tested by collecting data from questionnaires that were distributed in Indonesia. Based on a sample of 200 respondents, the results indicate that only social value has a positive impact on green consumer behavior, functional value (price), functional value (quality), environmental value, conditional value, epistemic value, and emotional value do not influence green consumer behavior. As a mediator, attitude toward green product has a significant effect on epistemic value, environmental value, and emotional value. This confirms and significantly adds to the literature of green consumer behavior in a developing market